Learning Math for 1st Grade Primary School Students using Intelligent Tutoring Systems - Amanda, Nadiran; Andersen, Felix; Christian, Ryan; Warnars, Harco Leslie Hendric Spits; Ramadhan, Arief; Putra, Arman Syah; Noordin, Nurulhuda; Utomo, Wiranto Herry (Turkish journal of computer and mathematics education, 2021)
Primary education after early childhood education is an important momentum in the education stage of a human being, in this case, education at the grade 1 level of elementary school. Where the delivery of subject matter properly and correctly at the early stages of this primary education will affect human education in the future. As well as the importance of early education at the elementary level, mathematics is an important initial subject to be given properly and correctly, so that the specter that says mathematics is a difficult subject is not true when a student in the early stages of basic education gets a good and correct mathematics education. Moreover, The Covid19 pandemic period is one of the parameters of the difficulty of knowledge transfer for students in the early stages of basic education, where physical meetings are not allowed to avoid Covid19 transmission in the classroom. Therefore, integrated tutoring systems (ITS) are a knowledge transfer tool that can help teachers, students, and parents in the delivery of subject matter, especially mathematics subjects which have a track record of being a scourge, scary and difficult to learn. In this paper, a simple ITS specifically for tutoring mathematics lessons for grade 1 elementary school students in Indonesia is tried to be implemented using the Unified Modeling Languages ​​(UML) tool as an object-oriented modeling tool. Use case diagrams are applied to describe business processes in the ITS system that we built and use class diagrams modeled database table designs. Not to forget, the user interface (UI) from the results of the implementation prototype was displayed as a communication medium for users, both children, and tutors, in using applications built using Personal Home Pages (PHP) and MySQL.